Research on Energy Management Strategy of Fuel Cell Electric Tractor Based on Multi-Algorithm Fusion and Optimization - Yang, Hongtu; Sun, Yan; Xia, Changgao; Zhang, Hongdang (Energies (Basel), 2022)
To solve the serious pollution problems of traditional fuel tractors and the short continuous operation time of pure electric tractors, a hybrid tractor with fuel cell as the primary power source and battery as the auxiliary power source is proposed. A novel energy management strategy was also designed, which integrates thermostat control strategy, power following strategy, and fuzzy logic control. The energy management strategy utilizes the advantages of different algorithms and realizes the rational distribution of fuel cell and battery output power. The system economy and fuel cell durability are improved by the tabu search algorithm. The simulation results show that the proposed energy management strategy can work well in different SOC states and reduce the fuel cell’s power fluctuations. The tractor is equipped with 960 g of hydrogen, the initial state of charge (SOC) is 90%, and it can operate continuously for 2.65 h.